Are Both Brand Awareness and Trust Play Significant Roles in Affecting Students’ Loyalty Toward Packaged Snacks Product? - Nicholas Wilson; Jessica Jessica (Journal of Business & Applied Management, 2020)
This study was conducted in order to determine whether brand awareness and trust have significant impact on university students’ loyalty toward packaged snacks that were usually sold in both supermarkets or convenience stores all across the region. This study implements survey method, in which, 250 active students from one of the private university in Jakarta participated as the respondents of this study. Students who were selected as the respondents in this study are those who’ve bought a packaged snacks product of any kinds (either biscuits, potato chips, corn chips, tortilla chips, and the other kinds of packaged snacks) at least 10 times for the past 6 months. Questionnaires then were used in order to collect the data from the respondents, and were electronically distributed to the respondents. After collecting all of the data, a total of 19 data need be deleted or omitted due to incomplete responses filled by the respondents. Therefore, a total of 231 usable data were further analyzed using PLS-SEM method in order to gain all of the results needed for concluding this study. Based on the results of the data analysis, authors concluded that both brand awareness and trust have significant impact on students’ loyalty toward packaged foods sold in many convenience store and supermarkets all across Jakarta, with Brand Awareness turns out to be the stronger predictor as compared to Trust. The results of this study then show the importance of improving or increasing people’s awareness toward the brand of the packaged snacks in order to bind people to be loyal to the brand. Furthermore, consumers’ trust toward the brand (and the all of the information attached to the label of the packaged snacks) also revealed to has a positive and significant role in enhancing people’s loyalty behavior toward the brand and the packaged snacks that were usually bought by the consumers.